Continuous improvement : seek perfection, assure quality at its source, embrace scientific thinking, focus on process, and improve flow & pull /: seek perfection, assure quality at its source, embrace scientific thinking, focus on process, and improve flow & pull. (2021) - Unknown
No abstract available